Normative Analysis: Regulatory Critique of Match Fixing Crimes in the 2018-2019 Liga 2 Football Competition. - NAYSILA RAMADHANI; Berlian Jelang Fajr (Indonesian Journal of Sports Law, 2025)
This article aims to analyze the legal framework governing matchfixing practices in the 2018–2019 Indonesian Liga 2 soccer competition and to identify weaknesses in the existing regulations. This study employs a normative legal method with a legislative approach. The findings indicate that match-fixing practices can, in principle, be prosecuted under the provisions of Law No. 11 of 1980 on Bribery Offenses; however, there are currently no specific regulations explicitly classifying match manipulation as a criminal offense under Indonesian positive law. This situation creates legal uncertainty and limitations in law enforcement, particularly regarding all forms of match manipulation. Therefore, regulations are needed to establish a specific offense related to match fixing to ensure legal certainty and the effectiveness of law enforcement in the field of sports.